PENERAPAN SANKSI ADAT BAGI PIHAK LAKI-LAKI YANG MENGHAMILI PEREMPUAN DILUAR PERKAWINAN DI DESA EMPACI - NIM. A1012161235, FEBRI KARDO KRISTIAN (Jurnal Fatwa Hukum, 2024)
Abstract  This thesis is entitled "Application of Customary Sanctions for Indigenous Village Dayak Community Couples Who Are Pregnant Outside of "Butang Customary" Marriage in Empaci Village, Sintang Regency." The problem under study is the application of customary sanctions for couples from Dayak indigenous people who are pregnant outside of marriage. "Butang custom" in Empaci Village, Sintang Regency, has it been implemented?" This research uses an Empirical Method whose research comes from the gap between theory and real life using hypotheses, theoretical foundations, conceptual frameworks, secondary and primary.The Butang custom in the Dayak Village community in Empaci Village is a serious violation which is believed to bring great disaster to the family and village community where the perpetrator lives, and is a taboo act in society so it needs to be brought to a customary case by paying a customary fine according to the act committed and the object. -Objects that are considered to have magical powers to restore magical peace that was disturbed due to the Butang custom. As time goes by, this is actually being looked down upon by perpetrators of violations of Butang customs who often only pay customary fines with money because it is easier and more practical and does not respect the tradition passed down from generation to generation regarding belief in objects that have magical value.Furthermore, this research was carried out in Empaci Village by collecting data through interviews and literature study. Based on the research results, it was concluded that what caused the Butang customary sanctions not to be implemented in the village Dayak community in Empaci village, Sintang district was due to environmental factors, technology and communication, as well as the most dominant religion.Keywords, Customs, Cases, Buttons    Abstrak    Skripsi ini berjudul "Penerapan Sanksi Adat Bagi Pasangan Masyarakat Adat Dayak Desa Yang Hamil Di Luar Perkawinan "Adat Butang" Di Desa Empaci Kabupaten Sintang." masalah yang diteliti Penerapan Sanksi Adat Bagi Pasangan   Masyarakat Adat Dayak Desa Yang Hamil Diluar Perkawinan"Adat Butang" Di Desa Empaci Kabupaten Sintang Telah Diterapkan ?". Penelitian ini menggunakan Metode Empiris yang penelitiannya berasal dari kesenjangan antara teori dengan kehidupan nyata yang menggunakan hipotesis, landasan teoritis, kerangka konsep, sekunder, dan primer.  Adat butang pada masyarakat Dayak Desa di Desa Empaci merupakan pelanggaran berat yang dipercaya akan mendatangkan malapetaka yang besar bagi keluarga dan masyarakat desa dimana pelakunya tinggal, dan merupakan perbuatan tabu dimasyarakat sehingga perlu dibawa ke perkara adat dengan membayar denda adat sesuai dengan perbuatan yang dilakkan serta benda-benda yang dianggap memilki kekuatan magis untuk memulihkan ketentraman magis yang sempat terganggu akibat perbuatan adat butang tersebut. seiring perkembangan zaman justru hal ini malah diremehkan pelaku pelanggaran adat butang justru sering kali hanya membayar denda adat dengan uang saja karena lebih mudah dan praktis dan tidak menghormti tradisi turun temurun akan kepercayaan pada benda yang punya nilai magis.  Selanjutnya penelitian ini dilakukan Di Desa Empaci dengan cara pengumpulan data melalui wawancara dan studi pustaka. Berdasarkan hasil penelitian, diperoleh kesimpulan bahwa Yang Menyebabkan tidak diterapkannya sanksi adat butang pada masyarakat dayak desa di desa empaci kabupaten sintang dikarenakan Faktor Lingkungan, teknologi Dan komunikasi, serta Agama Yang Paling Dominan.  Kata kunci, Adat, Perkara ,Butang